Intracellular Bacteria Interfere with Dendritic Cell Functions: Role of the Type I Interferon Pathway - Gorvel, Laurent (Public Library of Science, 2014)
Dendritic cells (DCs) orchestrate host defenses against microorganisms. In infectious diseases due to intracellular bacteria, the inefficiency of the immune system to eradicate microorganisms has been attributed to the hijacking of DC functions. In this study, we selected intracellular bacterial pathogens with distinct lifestyles and explored the responses of monocyte-derived DCs (moDCs). Using lipopolysaccharide as a control, we found that Orientia tsutsugamushi, the causative agent of scrub typhus that survives in the cytosol of target cells, induced moDC maturation, as assessed by decreased endocytosis activity, the ability to induce lymphocyte proliferation and the membrane expression of phenotypic markers. In contrast, Coxiella burnetii, the agent of Q fever, and Brucella abortus, the agent of brucellosis, both of which reside in vacuolar compartments, only partly induced the maturation of moDCs, as demonstrated by a phenotypic analysis. To analyze the mechanisms used by C. burnetii and B. abortus to alter moDC activation, we performed microarray and found that C. burnetii and B. abortus induced a specific signature consisting of TLR4, TLR3, STAT1 and interferon response genes. These genes were down-modulated in response to C. burnetii and B. abortus but up-modulated in moDCs activated by lipopolysaccharide and O. tsutsugamushi. This transcriptional alteration was associated with the defective interferon-β production. This study demonstrates that intracellular bacteria specifically affect moDC responses and emphasizes how C. burnetii and B. abortus interfere with moDC activation and the antimicrobial immune response. We believe that comparing infection by several bacterial species may be useful for defining new pathways and biomarkers and for developing new treatment strategies.